PERTARUNGAN IDENTITAS (KELUARGA) SAPI MADURA - Raditya, Ardhie (Universitas Wijaya Kusuma Surabaya, 2020)
So far, studies on the identity of Madurese bulls have not been adequately identified, especially the way of seeing of the Madurese bulls family. Madurese bulls are often seen as a secondary complement to the life of the Madurese. In fact, historically, metaphysically, and politically, Madures bulls are part of the 'close family' of the Madurese, whether we realize it or not. The power of the media industry, which has an impact on the cultural industry, has changed the identity of Madurese bulls as an industrial product. The advertisements for